Cross-border mergers and acquisitions: evidence from 10 developed countries / Nur Syazana Mohd Nasir ... [et al.] - Mohd Nasir, Nur Syazana; Kadir, Norsiah; Nayan, Sabri (2014)
This study attempts to explore the role of financial development on cross-border mergers and acquisitions (M&As) in 10 developed countries. Based on the sample period of 12 years (2000 – 2011), the data are analyzed by using dynamic panel data GMM estimator. Interestingly, we find that cross-border M&A respond positively and significantly to the stock market capitalization. The result highlights the importance of domestic financial conditions in stimulating an outward cross-border M&As during this period. Furthermore, the study also reveals evidence that market size (GDP) for host countries, trade inflation rate, exchange rate and Global economic crisis 2007/08 are statistically significant in influencing cross-border M&As from these 10 developed countries